A study of hereafter in Islam - Ashimi, Tijani Ahmad (Bangladesh Institute of Islamic Thought (BIIT), Dhaka, 2014)
The concept of hereafter which is also known in Islam as (Yawm al Qiyamah) is one of the basic article of Islamic faith, along with belief in God, His angels, His books and His Messengers, divine decree and predestination. In fact, in the most serious note, after the doctrine of unity of God (Tawhid) and revelation (al-wahy), the concept of hereafter is the most repeated theme with all vigour in the Islamic scripture (Qur’an). This implies, that all the tenets of Islam would be crumble and disintegrated if the afterlife or the eternal life were to be denied, as it will be very irrational to discuss the teaching of Islam and its tenets without referring to the great vitality that Hereafter (Al-akhirah) possesses, not only for man’s final end, but also for his life in this world. Based on this fact, this article will adopt textual and descriptive approaches to examine the hereafter in Islamic perspective, and its various names according to noble Qur’an will unequivocally be explored, a short discussion about its signs will be followed, and lastly the necessity and wisdom of this Islamic metaphysics will be explored.